Examining the Impact of Service Quality on Generation Z Customer Loyalty: Trust as a Mediating Variable in the MSME Sector - Ch Pangkey, Flowry; Ngadimin, Samat; Lule, Benny (Dinasti Publisher, 2026)
This study aims to analyze the influence of service quality on Generation Z customer loyalty in micro, small and medium enterprises in the creative screen printing and convection industry sector with trust variables as mediators. This study uses a quantitative approach by collecting data through questionnaires to three hundred and twenty-five Generation Z respondents who have ordered screen printing or convection services. Data analysis was carried out using structural equation modeling based on partial least square. The results of the study show that service quality has a positive and significant influence on customer loyalty. In addition, service quality also has a positive and significant effect on trust, and trust has a positive and significant influence on customer loyalty. The findings of the study also show that trust plays a role as a mediating variable in the relationship between service quality and customer loyalty. It was concluded that Generation Z's loyalty to micro, small and medium enterprises in the creative industry sector is not only influenced by the quality of service directly but is strengthened through the formation of trust first.